Digital transformation model based on business process management and lean manufacturing to increase the productivity of the administrative area of a peruvian aeronautical company - Ladera Mejia, Alexandra Gianella (2023)
The aviation sector has suffered the effects of the pandemic as the industry’s problems have become more evident due to operational constraints. The challenging and uncertain scenario has made the airline industry adapt its business to innovative alternatives based on efficient and digital strategies associated with the sector’s low productivity and the efficiency of each process. According to the reports, a series of failures were observed in the Maintenance Ad- ministrative Area, which is in charge of managing the work shifts of each technician in charge of aircraft maintenance, identifying that the most significant productivity problem in the area is based on the inefficient attention of requests to technical personnel. There- fore, a new model based on digital transformation was established by applying Business Process Management and Lean Manufactur- ing, in which the implementation of an ERP system connected to a self-service digital platform stands out. The main objective of this research is to increase productivity through the proposed new model and reduce unproductive times. Initially, the current case was analyzed, the improvements were identified, and the simulation was performed in the Arena software version 16; giving as a result of the validation, the increase of attention rate by 26.4%, the reduc- tion of the rejection rate by 2.09%, the increase of the registration efficiency by 32.59%, and a significant reduction of the cycle time by 87.37%; obtaining as a key result the increase of productivity by 18.62%, achieving a precedent that contributes to the optimization of the processes in the aeronautical sector.